Effect of Valproic Acid on Retina - M, Hayani; K, Wandarian (Journal of Ophthalmology and Research, 2019)
Anti-epileptic drugs (AEDs) are the main form of treatment for people with epilepsy. Around 70% epileptic patients may have their seizures controlled by taking these medications. Valproic acid is one of the most common drugs using for epileptic patients. This drug has some side effects like nausea, vomiting, bleeding, abdominal cramps, diarrhea, headache. In this research, we want to study on possible side effects of Valproic acid on eye in patients with epilepsy. Methods and Materials: In this study, we had 28 patients suffering from epilepsy and seizures who take Valproic acid for at least two years. The control group was included of 28 subjects with no history of taking this drug and no visual problem. Electroretinogram (ERG) obtained were compared with both groups to find possible changes. Results: The mean voltage of ERG was 92.98 ± 12.67 and 92.16 ± 13.47 μV in case and control groups, (P>0.05). The mean latency was 43.2 ± 3.06 and 44.80 ± 4.36 msec in case and control groups, with P>0.05. These findings show that there is no Significant difference in ERG parameters in case and control groups. Conclusions: By the result of this research, it can be concluded that Valproic acid does not have any side effects on the retina in patients taking this drug.